Rapidly self-healing idiopathic facial aseptic granuloma. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
Before the pediatric dermatologists of Bordeaux (1) identified the idiopathic facial aseptic granuloma and related it to infantile rosacea due to the frequent concurrence in the same subject of chalation we saw chronic self-healing inflammatory lesions of the face. However, we usually classified them as pseudolymphomas due to probable insect sting, especially when these lesions intervened in the summer. Exceptionally, the disease must be differentiated from an initial chronic granulomatous disease (2). The current child is the fastest – about a month – self-healing case described so far. The decision to monitor the current case clinically without any therapy depended on the unanimous agreement on the spontaneous regression of the disease and also on the presumed efficacy of the most disparate therapies from intralesional corticosteroids to antibiotics.